Определение направлений использования профилированных заготовок после подготовительной осадки штамповыми вставками различной конфигурации - Кухарь, В. В. (НТУ "ХПИ", 2014)
Проанализированы особенности формоизменения заготовок при осадке штамповыми вставками с плоской, выпуклой и конической геометрией рабочей поверхности. Выполнена систематизация и сопоставление конфигураций профилированных заготовок, полученных способами осадки, с базовой номенклатурой поковок, штампуемых на прессовом оборудовании. Определены структурные составляющие технологий штамповки типовых изделий различной номенклатуры на основе предварительного профилирования заготовок осадкой штамповыми вставками различной геометрии

Specifics of form changing of work-pieces during upsetting by die-plates with flat, convex and conical geometry of work surface are analysed. The systematisation and comparable analyze of form of shaped billets worked by upsetting with based nomenclature of forging-parts worked by press equipment were executed. Structures steps of technique of impression die-forging for receiving types of different nomenclatures worked parts are determinate on the base of preparing profiling of work-pieces by upsetting on die-plates with different configuration
Defining the usage direction of profiled blanks after preparative draft with sinterchangeable stamping equipment of different configurations
Keywords: металлообрабатывающая отрасль; профилирование; формоизменение; объемная штамповка; номенклатура поковок; billet; profiling; upsetting; form changing; die-plates; volumetric impression die-forging; determination of nomenclatures of forging-parts